CRITICAL REVIEW OF TELEPHARMACY SERVICES AND ASSESSING ACCESSIBILITY, CLINICAL SUPPORT, AND MEDICATION ADHERENCE IN REMOTE HEALTHCARE SETTINGS - Salem Saaed Aljarah, Al-Hassan Rashid Mahdi Al-Shaita, Bader Abdullah Salehalabaas, Abdullah Ali Alqarzan, HadiMusfer Ali Algashaneen, Moslih Mana Hadi Almakaeel, Meshal Saud Saleh Al Harith, Eabdallah Saud Salih Alharith (Chelonian Research Foundation, 2022)
Telepharmacy is a reasonably appealing answer to extend healthcare and make it an affordable commodity in the market, particularly in far-off and deprived regions. This critical appraisal looks at the vital function of telepharmacy in increasing accessibility, offering clinical assistance, and, most importantly, adherence to medication use in remote healthcare settings. This paper scrutinizes vital elements of telepharmacy by analyzing the extant literature, including evidence and the limitations of telepharmacy. The key elements, like legal frameworks, technological infrastructure, and patient involvement dynamics, are inspected here to understand the complexity of telepharmacy integration. This study showed evidence of telepharmacy as a practical measure that enhances health access and, ultimately, the patient's outcome. The research also highlighted the areas requiring further research and development. Keywords: telepharmacy, remote healthcare, accessibility, clinical support, medication adherence, healthcare disparities